A DEVELOPMENT MODEL OF FUZZY GOAL PROGRAMMING FOR REGIONAL RIVER WATER QUALITY MANAGEMENT - Udisubakti Ciptomulyono (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
This paper proposes a development of Fuzzy Goal Programming model with imprecise information goal for optimizing the regional water quality management. Imprecision is associated with fuzziness which is non-statistical in nature and refers to the absence of sharp boundary in the information. Imprecise standards in environmental management objective could be represented by fuzziness functions. The objectives of management to be achieved in this model are categorized as: (i) Environmental objectives i.e. to maintain an ambient water quality in two parameters and standards, BOD(Biochemical Oxygen Demand) and DO (Dissolved Oxygen) closed to desired stream standard goal and to achieve an improvement sanitation program target;(ii) Economic objective i.e. to minimize the total cost of removing residual by an alternatives waste of treatment systems. The model of